Students' Perceptions of the Movie Story of Joy Inspiring Entrepreneurs - Hendra Poltak; Tio Arriela Doloksaribu; Muhfizar Muhfizar; Endang Gunaisah; Mustasim Mustasim (Budapest International Research and Critics University, 2021)
Movie have an influence in creating audience perceptions and playing attitudes, behaviors, and actions. This study aims to determine student perceptions of the joy film story that inspires entrepreneurship. Qualitative descriptive research approach is used to determine the perception of the film Joy. Selected informants as many as 3 students who can retell the film Joy for students have watched so it is easy to confirm the information. The results of the interview show that Joy's film has a positive perception of the struggle of the entrepreneur character Joy and inspires students to intend to become entrepreneurs.